Structure, Optical Properties, and Photocatalytic Activity towards H2 Generation and CO2 Reduction of GaN Nanowires via Vapor-Liquid-Solid Process - Hong Pang; Lequan Liu; Shuxin Ouyang; Hua Xu; Yunxiang Li; Defa Wang (International Journal of Photoenergy)
High quality single crystalline GaN nanowires with large aspect ratio (>100) are synthesized on n-type Si (111) substrate via Au-catalyzed vapor-liquid-solid process. Morphology, crystal structure, and optical property of the as-synthesized GaN nanowires are characterized by means of X-ray diffraction, scanning/transmission electron microscopy, UV-vis diffuse reflection spectroscopy, and room temperature photoluminescence. The results indicate that the as-prepared GaN nanowires with a large aspect ratio are well crystallized in the hexagonal wurtzite structure, and a slight blue shift appears in both the absorption edge and emission peak probably due to the quantization effect. Photocatalytic H2 evolution over the as-prepared GaN nanowires is performed with the incorporation of Pt or Rh as the cocatalyst, exhibiting greatly enhanced capability compared to the GaN powder tested under the same conditions. Moreover, photocatalytic CO2 reduction over the GaN nanowires is also successfully realized using Pt or Rh as the cocatalyst, depending on which the products show a strong selectivity inherently related to the reductive electrons transferred by cocatalyst.